The Formation of the Anthroposen - The Impact of the Preaching of the Risen Christ - Isriyanto, Isriyanto; Sembiring, Milisi; Sitepu, Edward; Wijaya, Yulius; Nugraeni, Giarti (Journal of Ecohumanism, 2024)
The importance of the seeds of the Gospel being sown in cultural and religious treasures requires accurate observation. The preacher of the Gospel, in this case the Prophet Paul, who was rooted in Judeo-Christianity, was very aware of the religious cultural aspect as a bridge for planting the seeds of the Gospel to produce new humans. In the conditions that occurred in Acts 17 on his second missionary journey, the Areopagus was a platform for preaching about the resurrection of Christ to the people of Athens who were rational in philosophy but still limited in understanding. Namely understanding the relationship between humans and God. This article highlights these aspects by using a reflective grammatical approach to issues of human experience, expressions and actions, the diction of the unknown God and the importance of the risen Christ. The findings show that the presence of new social relationships is inevitable. This is traced based on Habermas’ theory which emphasizes the function of communication in social relations.